Transmit diversity for TS-OFDM signal in higher time-varying fading channels - Danchai, Anusan; Reangsuntea, Arttapol; Boonsrimuang, Pisit; Reangsuntea, Pongsathorn; Mori, Kazuo; Kobayashi, Hideo (My University, 2017)
This paper proposes a channel estimation and equalization methods for a transmit diversity system of using time domain training sequence inserted orthogonal frequency division multiplexing (TS-OFDM) signal in higher time-varying fading channels. The salient feature of the proposed channel impulse response (CIR) estimation method for the transmit diversity system with a space frequency block coding is to employ a new design of training sequence (TS) signal which can reduce the leakage of power spectrum density (PSD) and keep higher CIR estimation accuracy. In the proposed equalization method, the estimated CIR at every sampling time and the known TS signals are employed at the receiver for removing the inter-symbol interference (ISI) caused in higher time-varying fading channels so as to employ the overlap and add (OLA) operation. This paper presents various simulation results to demonstrate the effectiveness of the proposed transmit diversity system as comparing with the conventional methods.
Keywords: Channel estiamtion; OLA; Power spectrum density; Training sequence; Transmit diversity; TS-OFDM